The effect of vaginal evening primrose on the Bishop score of term nulliparous women - Motahareh Najafi; Marzeyeh Loripoor; Zahra Saghafi; Majid Kazemi (Tehran University of Medical Sciences, 2019)
Background & Aim: Desirable bishop score is necessary for having a successful delivery. Prostaglandins are effective on cervical ripening and primrose contains precursors of these materials. Therefore, the present study was conducted to evaluate the effect of vaginal Evening primrose on the bishop score among term nulliparous women. Methods & Materials: The present double-blind randomized clinical trial was conducted on 86 nulliparous women who referred to the comprehensive health service centers of Rafsanjan from November 2017 to May 2018. The samples were selected through convenient sampling method and allocated into two intervention and placebo groups with simple random assignment. The intervention group used a daily dose of 1000 mg vaginal capsules of Evening primrose from the 38th week of pregnancy until delivery and the placebo group received similar placebo with similar administration method. The Information about the women's bishop score was gathered from the participants' medical files in the hospital and then was analyzed using SPSS software version 16 and Kolmogorov-Smirnov test, Chi-square test and independent t-test. Results: The total mean and standard deviation of the bishop score in the intervention and placebo groups was respectively 7.83 ± 2.09 and 4.46 ± 2.39 and the simplified bishop score in the intervention and the control groups was respectively 5.93 ± 2.42 and 2.81 ± 2.02. The difference between the two groups considering both of the bishop scores was statistically significant (p = 0.001). Conclusion: Vaginal Evening primrose is effective to ripen the cervix of term nulliparous women and so, it could be administered for this purpose.